Evaluating the Asymmetry of Muscle Activation and Strength in Paralympic Powerlifting Athletes - Leonardo dos Santos; Felipe J. Aidar; Rafael Luiz Mesquita Souza; Dihogo Gama de Matos; Stefania Cataldi; Gianpiero Greco; Márcio Getirana-Mota; Anderson Carlos Marçal; Lucio Marques Vieira Souza; Jymmys Lopes dos Santos; Paulo Francisco de Almeida-Neto; Breno Guilherme de Araújo Tinoco Cabral; et al. (MDPI AG, 2023)
Background: Strength training is a complex task, as it requires a combination of many variables. In paralympic powerlifting (PP) asymmetries for the evaluation of activation, and static force indicators have been increasingly studied. Objective: To investigate the asymmetries in the strength and muscle activation indicators, before and after a training session of PP athletes. Methodology: Twelve elite athletes from the PP participated in the study, and asymmetry was evaluated through surface electromyography (sEMG) and static strength indicators. Evaluations were made before and after a protocol of five series of five repetitions (5 × 5), with 80% of 1-Maximum Repetition (1RM). Results: In the pectoral muscles, there were differences in the non-dominant limbs between the before and after in the sEMG. There were differences in the pectoralis muscle in the non-dominant limb between moments before (110.75 ± 59.52%) and after (130.53 ± 98.48%, p < 0.001), and there was no difference in triceps activation. In the Maximum Isometric Strength (MIF), there was a difference in the non-dominant limb between before (710.36 ± 129.36) and after (620.27 ± 69.73; p < 0.030). There was a difference before in the dominant (626.89 ± 120.16; 95% CI 550.55-703.24) and non-dominant (710.36 ± 129.36; p = 0.011) limbs. There was no difference in time to MIF. Conclusion: PP athletes showed small levels of asymmetry before and after training, and adaptation to training tends to promote fewer asymmetries.